2019
DOI: 10.1186/s12887-019-1744-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the vitamin D and biomedical statuses of young children with β-thalassemia major at a single center in southern China

Abstract: BackgroundIn young children, β-thalassemia major (β-TM) is associated with potentially severe clinical characteristics, including poor growth, feeding difficulties, hepatosplenomegaly, bone metabolic disorders, and skeletal abnormalities.MethodsIn this study, we reviewed the demographic and clinical characteristics (e.g., age, sex, duration of blood transfusion and chelating therapy, and vitamin supplementation) and serum biomarker levels (e.g., iron accumulation, bone metabolism, liver, kidney, and thyroid fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Our study revealed that 6.9% of patients have osteopenia and 6.9% have osteoporosis. Vitamin D deficiency frequency was 72.41% and was similar to prior studies, which have reported as 54%, 69.8%, and 90% 10 , 15 , 16 . Vitamin D deficiency is thought to be related to hepatic dysfunction and defective vitamin D hydroxylation due to iron overload 17 .No significant relationship or correlation was determined between vitamin D and ferritin.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study revealed that 6.9% of patients have osteopenia and 6.9% have osteoporosis. Vitamin D deficiency frequency was 72.41% and was similar to prior studies, which have reported as 54%, 69.8%, and 90% 10 , 15 , 16 . Vitamin D deficiency is thought to be related to hepatic dysfunction and defective vitamin D hydroxylation due to iron overload 17 .No significant relationship or correlation was determined between vitamin D and ferritin.…”
Section: Discussionsupporting
confidence: 89%
“…Vitamin D deficiency is thought to be related to hepatic dysfunction and defective vitamin D hydroxylation due to iron overload 17 .No significant relationship or correlation was determined between vitamin D and ferritin. Yu et al’s 16 study revealed normal vitamin D levels in patients <5 years and that the deficiency progressively increased with age. Our study revealed no significant difference between the age groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Both Nakavachara and Viprakasit 61 and Fung et al 62 found that non-transfusion-dependent subjects with Thal had significantly lower 25(OH)D than transfusion-dependent subjects, perhaps due to infrequent visits with medical personnel and inadequate nutrition monitoring. Lumbar spine bone mineral density (BMD) positively correlated with 25(OH)D. 42,63,64 Both Claster et al 12 and Wood et al 57 found that age was negatively correlated with 25(OH)D. Furthermore, Yu et al 24 found older subjects with Thal to have lower absolute 25(OH) D, perhaps related to reduced time spent outdoors compared with younger subjects. In contrast, Vogiatzi et al 65 observed that adolescents with Thal residing in the United States had lower 25(OH)D than children or adults, possibly related to increased time indoors at school.…”
Section: Vitamin D and Calciummentioning
confidence: 99%